2019
DOI: 10.1111/rec.13078
|View full text |Cite
|
Sign up to set email alerts
|

Are we close enough? Comparing prairie reconstruction chronosequences to remnants following two site preparation methods in Missouri, U.S.A.

Abstract: Prairie reconstruction has become a common method for reestablishing tallgrass prairie communities in the central United States. With the objective of creating plant communities that approximate remnant (reference) prairies, managers are interested in identifying: (1) best methods for reconstructing reference community conditions; (2) the rate of change in plant communities through time following reconstruction; and (3) species present in remnant communities but missing from reconstructed communities. This inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…The overall increase in C cwm is encouraging from the standpoint of successful reconstruction of a high-quality prairie community. Cvalues increased quickly in the first 6-8 years after prairie plantings in Iowa (Carter & Blair, 2012) and Missouri (Newbold et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The overall increase in C cwm is encouraging from the standpoint of successful reconstruction of a high-quality prairie community. Cvalues increased quickly in the first 6-8 years after prairie plantings in Iowa (Carter & Blair, 2012) and Missouri (Newbold et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The overall increase in C cwm is encouraging from the standpoint of successful reconstruction of a high‐quality prairie community. C ‐values increased quickly in the first 6–8 years after prairie plantings in Iowa (Carter & Blair, 2012) and Missouri (Newbold et al, 2020). However, over a longer time more comparable to our study, Hansen and Gibson (2014) found that mean C ‐values decreased over a 20‐year chronosequence of prairie restorations at Nachusa Grasslands in Illinois.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the older PFCA sites (9 to 13-yr) were previously under long-term cultivation for more than 20 yr (personal communication with Jeff Demand, site historical manager). The prairie reconstruction at PFCA employs a variety of management strategies and techniques, including: (1) site preparation; (2) seeding native plants collected from nearby native prairies (<75 km) including Tucker Prairie; and (3) mowing, prescribed fire, and exotic species control for establishment and maintenance of the natural plant communities (Newbold et al, 2019). Site preparation included two treatments to remove undesirable species: (1) 3-, 4-, 6-, 9-, 13-yr PFCA were prepared using notill cropping of glyphosate-resistant crops (e.g., soybeans or corn) for ≥3 yr prior to seeding prairie species; and (2) 2-, 10-, 11-, 12-yr sites were prepared using nonnative and native grass planting followed by 1-2 yr of herbicide applications.…”
Section: Sites Description and Soil Samplingmentioning
confidence: 99%
“…In many ecosystem reconstruction projects, parameters increase rapidly during the first several years then level off in late successional conditions (Brown, 1991;Baer et al, 2002). A plant community study conducted at PFCA in July 2017 found that native plant community indices (floristic quality and species richness) initially increased with prairie reconstruction, but plateaued after 4-yr and did not decline (Newbold et al, 2019). Other studies have reported declines in older reconstruction sites (Sluis, 2002;Camill et al, 2004;Hansen and Gibson, 2014).…”
Section: Apparent Decline In Soil Health 8-yr Post-reconstructionmentioning
confidence: 99%
“…Greater than 180 species of grasses and forbs were established in the reconstructed prairies on PFCA, including many species with high coefficients of conservatism (Ladd and Thomas 2015, Newbold et al 2019). However, as a result of grass competition, milkweeds and other forbs were not as abundant as desired.…”
Section: Study Areamentioning
confidence: 99%